Adequacy of micronutrient fortification in the mandatory fortified food vehicles in Tanzania. Issue 4 (24th August 2020) - Kiwango, Flavia Andrew; Chacha, Musa; Raymond, Jofrey
Abstract : Purpose: This study aims to update the information on the current status of micronutrient fortification for iron, zinc, folic acid and vitamin A in mandatory fortified food vehicles such as cooking oil, wheat and maize flours in Tanzania. Design/methodology/approach: A cross-sectional study was conducted in five regions to analyze the adequacy of micronutrient fortification in mandatory fortified food vehicles. Samples of fortified edible oil ( n = 19), wheat flour ( n = 12) and maize flour ( n = 5) were sampled conveniently from local markets and supermarkets. Samples were analyzed for vitamins (vitamin A and folic acid) and mineral (iron and zinc) content using high-performance liquid chromatography and microwave plasma-atomic emission spectrometer, respectively. Compliance acceptable ranges between the minimum and maximum levels for each nutrient were used as a basis for compliance. Findings: The results showed that 83.3% and 80% of wheat and maize flour samples, respectively, complied with iron fortification standards ( p = 0.05). Only 25% of wheat flour samples and 40% of maize flour samples were within the acceptable ranges for zinc fortification ( p = 0.05). Nearly 17% and 20% of wheat and maize flour samples, respectively, were within the acceptable ranges for folic acid fortification ( p = 0.05). Moreover, about 10.5% of the analyzed cooking oils were adequately fortified with vitamin A ( p = 0.05). Except for iron in wheat and maize flours, the levels of other micronutrients in mandatorily fortified foods were out of acceptable ranges. Originality/value: Mandatory fortification is still far from the established standards, and this calls for a review of the current fortification strategies regarding standards, training, monitoring and enforcement in Tanzania.